2019
DOI: 10.1210/clinem/dgz015
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction Induced by High Estradiol Concentrations in Endometrial Epithelial Cells

Abstract: Context A supraphysiological estradiol (E2) concentration after ovarian stimulation is known to result in lower embryo implantation rates in in vitro fertilization. Endometrial epithelial cell (EEC) apoptosis occurs after the stimulation with high E2 concentrations, and mitochondria play important roles in cell apoptosis. Objective To investigate the mitochondrial function in EECs after the stimulation with high E2 concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Others reported that long-term E2 treatment increased nuclear respiratory factor-1 (NRF-1) protein in cerebral blood vessels of ovariectomized rats [15]. Interestingly, high estradiol concentrations (about 10-8 M) decrease the mitochondrial DNA contents, and ATP formation and these effects were not showed at minor concentrations [16,17]. For this reason, in this work, we study the effect of estradiol at low concentrations.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Others reported that long-term E2 treatment increased nuclear respiratory factor-1 (NRF-1) protein in cerebral blood vessels of ovariectomized rats [15]. Interestingly, high estradiol concentrations (about 10-8 M) decrease the mitochondrial DNA contents, and ATP formation and these effects were not showed at minor concentrations [16,17]. For this reason, in this work, we study the effect of estradiol at low concentrations.…”
Section: Introductionmentioning
confidence: 89%
“…We inserted the E-plate 16 into a cradle pocket of the RTCA DP analyzer, and we performed blank reading to measure the background impedance of cell culture media. We added 100 μl of a cell solution with a final concentration of 2500 cells/well in the E-plate 16 e specific PCR products were detected by the fluorescence of SYBR Green, the doublestranded DNA binding dye. Primers were designed using BLAST ® (Basic Local Alignment Search Tool, NBCI, NIH), considering the shortest amplicon proposed: primers' sequences are shown in Table 1, and β-actin was used as the housekeeping gene.…”
Section: Real-time Monitoring Of Cell Proliferationmentioning
confidence: 99%
“…According to previous reports, when E2 levels reach a certain threshold, the adverse effects of high E2 levels on endometrial receptivity may be related to weakened endometrial blood flow ( 36 , 37 ), enhanced uterine contractility ( 38 ), interference with glycogen synthesis and secretion ( 39 ), intrauterine histopathological changes of nuclear amygdala channels ( 40 , 41 ), and changes in mitochondrial function ( 26 , 42 ). High E2 concentrations also promoted the apoptosis of endometrial gland cells in a positive feedback pathway, further damaging the receptivity of the endometrium ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…High estrogen concentration is seen in women with PCOS that enhances extra mitochondrial oxidative stress in endometrial cells and leads to decreased implantation and poor pregnancy rates ( 14 ). In our study, women treated with combination had better conception rate and better endometrial thickness at the time of trigger.…”
Section: Discussionmentioning
confidence: 99%